Technology Adaptation and CEO Characteristics: Enhancing Competitive Advantage in Indonesia’s MSME of F&B in the Jabodetabek Region - Awwal, Muhammad Al Faridho; Utami, Eva Yuniarti; Sumerli A, Chevy Herli; Purwoko, Bambang (International Journal of Business, Law, and Education, 2023)
The food and beverage (F&B) industry significantly impacts Indonesia's economy, playing a crucial role in economic growth and welfare. Micro, small, and medium-sized enterprises (MSMEs) in the F&B sector, particularly in the Jabodetabek region, are essential contributors to Indonesia's global standing. This study explores the relationship between technology adaptation, CEO characteristics, and competitive advantage in Jabodetabek's F&B MSMEs. Challenges faced by these enterprises, such as limited resources and human capital, underscore the need for effective technology adoption and strong leadership. The research aims to enrich the literature on this subject and provide insights for policymakers to enhance MSME competitiveness.